Оправданоста на војувањето и шестата Божја заповед од православна перспектива - Gogovski Stefan; Micevski-Ignat Ilche (Православен Богословски факултет „Св. Климент Охридски“ - Скопје, 2025)
The paper focuses on reviewing, exploring, answering and presenting the Christian norms and positions in relation to war and warfare from Orthodox ethical and canonical perspective. The Orthodox understanding of warfare and the use of force differs from the Western and secular ‘just war theory’, which means the way of the Orthodox attitude towards the problem of justifaing warfare is not present, because war is always seen as unconditional ‘evil’. The reason why the Church hasn’t developed a socalled ‘just war theory’ is because of the fact that The Church of Christ is always leaned towards peace. Thus said, warfare is actually understood as an unconditional evil, caused by pride, hatred and human abuse of the God given freedom. In no case could war, or an intiation of a military conflict be justified, for the reason that the Orthodox Church does not justify or favor the manifestation of evil in any of its forms, especially when it comes to a form of evil that is directly aimed at endangering someone’s well-being and life.
Keywords: War Conflict; Ethics; Christian context